Performance Determination - Fauzi Hasibuan, Leo; Farida Ferine, Kiki (PT. Multidisciplinary Press Indonesia, 2024)
This research was conducted to determine the influence of human resource quality and work ethics on employee performance with organizational commitment as an intervening variable at the Bank Indonesia Representative Office, North Sumatra Province. Effective and efficient achievement of company goals requires the continuous implementation of internal human resource management. The efficacy and efficiency of a company greatly depends on the advantages and disadvantages of resource development. This means that the company's human resources must be developed and nurtured in order to be able to improve their work capabilities, which will ultimately have an impact on improving performance. The results of this research are as follows: Work Ethics has a positive and insignificant effect on Employee Performance with the original sample being 0.079 and p value 0.322. Work Ethics has a positive and significant effect on Organizational Commitment with the original sample being 0.665 and p value 0.000. Organizational Commitment has a positive and significant effect on Employee Performance with an original sample value of 0.831 and ap value of 0.000. HR quality has a positive and insignificant effect on employee performance with an original sample value of 0.020 and ap value of 0.428. HR quality has a positive and significant effect on Organizational Commitment with an original sample value of 0.263 and ap value of 0.006. Work Ethics has a positive and significant effect on Employee Performance through Organizational Commitment indirectly with an original sample value of 0.552 and ap value of 0.000. HR quality has a positive and significant effect on employee performance through organizational commitment indirectly with the original sample being 0.218 and p value 0.009.